2011
DOI: 10.1159/000322742
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Preeclampsia Using Inhibin A and Other Second-Trimester Serum Markers

Abstract: Objective: The purpose of this study was to determine whether second-trimester maternal serum markers including inhibin A are useful for the detection of preeclampsia. Methods: Between January 2005 and March 2009, we analyzed the data of 4,764 subjects who underwent second-trimester multiple-marker screening for Down syndrome. Serum samples were assayed at 15+0 to 20+6 weeks for maternal serum alpha-fetoprotein (MSAFP), human chorionic gonadotrophin (hCG), unconjugated estriol (uE3) and inhibin A. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…Ree et al . examined the performance of second trimester biochemical markers in the screening for pre‐eclampsia and found that, when using beta‐hCG with a cut‐off of 2.5 MoM, detection and false positive rate is 17.0% and 4.2% …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ree et al . examined the performance of second trimester biochemical markers in the screening for pre‐eclampsia and found that, when using beta‐hCG with a cut‐off of 2.5 MoM, detection and false positive rate is 17.0% and 4.2% …”
Section: Discussionmentioning
confidence: 99%
“…cut-off of 2.5 MoM, detection and false positive rate is 17.0% and 4.2%. 21 It was suggested that increased AFP is related to a disruption at the fetal-maternal interface, thus permitting transfer of AFP into the maternal circulation. 22 Abnormally increased levels of hCG may be because of decreased placental perfusion with subsequent reduced oxygenation of the cytotrophoblast.…”
Section: Wiedemann Syndromementioning
confidence: 99%
“…Concentrations of circulating dimeric inhibin-A rapidly rise in early pregnancy, fall after 12 weeks of gestation, remain low in the second trimester, and gradually increases in the latter half of pregnancy (29, 30). Previous studies did not report associations of Inhibin-A both at ≤5 th and ≥95 th percentiles in relation to abruption.…”
Section: Discussionmentioning
confidence: 99%
“…Інгібін А насправді є найважливішим передбачуваним маркером. Результати цього дослідження підтверджують результати попередніх досліджень та надають кількісні дані, що вказують на виникнення ПЕ [28]. Враховуючи результати цього дослідження, можна зробити висновок, що MOM рівня інгібіну А у материнській сироватці крові під час другого етапу тестів на скринінг вагітності дозволяє прогнозувати частоту та тяжкість розвитку прееклампсії у вагітних жінок [7].…”
Section: акушерство та гінекологіяunclassified